Improving science teachers’ nature of science views through an innovative continuing professional development program - Erdas Kartal, Eda; Cobern, William W.; Dogan, Nihal; Irez, Serhat; Cakmakci, Gultekin; Yalaki, Yalcin (Springer Science and Business Media LLC, 2018)
This study describes how teachers' nature of science (NOS) views changed throughout an innovative Continuing Professional Development (CPD) program that provided sustained support throughout the process in a collaborative and reflective environment and activities that are consistent with the current curriculum and NOS tenets integrated within. Eighteen in-service science teachers enrolled in a yearlong nature of science, Continuing Professional Development (NOS-CPD) program. Data were collected by pre/post-interviews using the Views of Nature of Science-Form C (VNOS-C) questionnaire, and a post-interview using an open-ended questionnaire developed by researchers to uncover teacher reactions to the NOS-CPD program.The results indicated that the NOS-CPD program improved the teachers' NOS views more effectively than previously reported short-term teacher development programs, and thus, the findings should be useful for future studies in support of the professional development of teachers.The article concludes with practical advice for implementing NOS-focused, in-service teacher development programs.
Keywords: IDEAS; Teacher education; STUDENTS; Theory and practice of education; INQUIRY; Education; Teacher Education; TEACHING NATURE; Nature of Science; L7-991; CONCEPTIONS; Science education; LB5-3640; Professional Development; LC8-6691; Research; Professional development; Education (General); L; Special aspects of education; Nature of science; Science Education; 4. Education; 3. Good health; 13. Climate action